Algunas especies de Hypoxylon (Pyrenomycetes, Xylariaceae) de México - San Martin, Felipe Eduardo; Ju, Yu-Ming; Rogers, Jack D. (Instituto de Ecología, A.C., 1999)
An artificial key to 41 species and 3 varieties of the genus Hypoxylon sensu stricto collected in Mexico so far, is presented; 31 species and one variety belong to section Hypoxylon whereas 10 species and 2 varieties correspond to section Annulata. Two taxa remain without specific epithet due the scarcity of the material or the lack of anamorphic data. The new variety Hypoxylon shearii var. minor is proposed. Data on distribution, substrates, collecting dates, and affinities with other species of the genus, are provided for most taxa.